2015
DOI: 10.5056/jnm14008
|View full text |Cite|
|
Sign up to set email alerts
|

Alterations of Colonic Contractility in an Interleukin-10 Knockout Mouse Model of Inflammatory Bowel Disease

Abstract: Background/Aims Inflammatory bowel disease is commonly accompanied by colonic dysmotility and causes changes in intestinal smooth muscle contractility. In this study, colonic smooth muscle contractility in a chronic inflammatory condition was investigated using smooth muscle tissues prepared from interleukin-10 knockout (IL-10 −/− ) mice. Methods Prepared smooth muscle sections were placed in an organ bath system. Cholinergic and nitrergic neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…After discarding 1 cm from the cecum and anus, 5 cm of the proximal and distal parts of the colon were collected from each. 33,39 A part of each sample 1 cm in length was prepared for histological analysis by fixation in 10% buffered formalin. The tissue specimens embedded in paraffin blocks were cut perpendicularly to the lumen into 4 μm thick sections and then stained with hematoxylin and eosin.…”
Section: Tissue Preparationmentioning
confidence: 99%
“…After discarding 1 cm from the cecum and anus, 5 cm of the proximal and distal parts of the colon were collected from each. 33,39 A part of each sample 1 cm in length was prepared for histological analysis by fixation in 10% buffered formalin. The tissue specimens embedded in paraffin blocks were cut perpendicularly to the lumen into 4 μm thick sections and then stained with hematoxylin and eosin.…”
Section: Tissue Preparationmentioning
confidence: 99%
“…In fact, in pathological conditions characterized by inflammation, gut segment spontaneous contractility is altered. 35 Pres Phytum affects spontaneous contractility of stomach, but no effect is obtained at the concentration effective on the cardiovascular system. This effect may result in a slight decrease of gastric emptying frequency.…”
mentioning
confidence: 97%
“…The findings from this paper suggest that IL-10 immunodeficient mice might be an attractive model for researching IBD including Crohn's disease. 1,5 In addition, this study's investigation of the function and expression level of muscarinic type 2 (M 2 ) receptors is worthwhile in that the M 2 receptors may play a greater role in the inflamed colon. 6,7 These considerations make the article a strong one, and its conclusions can serve as a stepping stone to investigate several unanswered problems in gastrointestinal (GI) smooth muscle biology as follows.…”
mentioning
confidence: 99%
“…4 The animal model used in this study, however, showed inflammatory cell infiltration in all colonic layers (including the muscular layer) and exhibited lesions similar to those found in Crohn's disease. 1 This paper does take a novel approach by studying changes in smooth muscle and motility in an immunodeficiency model. The findings from this paper suggest that IL-10 immunodeficient mice might be an attractive model for researching IBD including Crohn's disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation